PENINGKATAN KINERJA PEGAWAI DI BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN MANGGARAI YANG DIPENGARUHI OLEH FAKTOR KEPEMIMPINAN TRANSFORMASIONAL DAN REWARD - Wigberta Jeliut; Muninghar; Fatimah Riswati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
This type of research is explanatory research, the research approach uses a quantitative approach, data analysis uses SPSS. The research sample was 77 employees. The objectives of this study are 1). To describe transformational leadership, reward and employee performance of the General Section of the Regional Secretariat of Manggarai Regency. 2). To test and manage transformational leadership leadership, reward simultaneously have a significant effect on employee performance 3). To test and analyze whether transformational leadership has a significant influence on employee performance. 4). To test and analyze whether the reward has a significant effect on the performance of the employees of the General Section of the Regional Secretariat of Manggarai Regency. 1). Simultaneously, transformational leadership, reward and have a significant effect on employee performance at the General Section of the Regional Secretariat of Manggarai Regency. It is proven that the results of the calculated F value is 2.903 with an unknown significance level of the sig value, which is 0.003 (less than 0.05). 2). Partially, transformational leadership, reward have a significant effect on employee performance at the General Section of the Regional Secretariat of Manggarai Regency. 3). Based on the test results, it is known that transformational leadership has an effect on employee performance on employee performance at the General Section of the Regional Secretariat of Manggarai Regency; as evidenced by the t value is 1,400 with a significance level of 0.003 (less than 0.05).